2013
DOI: 10.5430/ijhe.v2n3p139
|View full text |Cite
|
Sign up to set email alerts
|

Critical Thinking in College Freshmen: The Impact of Secondary and Higher Education

Abstract: Critical thinking helps students to confront a multitude of challenges they will face in their carreers and personal lives. It is therefore an important task of higher education to promote students' critical thinking. However, students do not enter higher education as a blank slate. Background characteristics of students are important in developing instruction. The present study investigates the influence of an important background characteristic, namely students' secondary education, and their current higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 28 publications
3
27
0
1
Order By: Relevance
“…On the other hand, disciplinary differences could be due to individual characteristics that impact when time comes to enroll in a particular course from a certain disciplinary area (Badcock et al, 2010), seeing that neurocognitive systems, in interaction with life experiences, are responsible for individual differences in CT (Bolger, Mackey, Wang, & Grigorenko, 2014). Also, it is necessary to account for the impact of educational background, as suggested by Evens, Verburgh, and Elen (2013), who found that Secondary Education impacts the choice of disciplinary area, which relates to students' CT performance. Overall, CT differences may be mostly due to pedagogical practices, so "educators will need to study the practices of exemplary instructors rather than exemplary disciplines, because no disciplines appear to stand out in this domain" (Brint et al, 2012, p. 22).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, disciplinary differences could be due to individual characteristics that impact when time comes to enroll in a particular course from a certain disciplinary area (Badcock et al, 2010), seeing that neurocognitive systems, in interaction with life experiences, are responsible for individual differences in CT (Bolger, Mackey, Wang, & Grigorenko, 2014). Also, it is necessary to account for the impact of educational background, as suggested by Evens, Verburgh, and Elen (2013), who found that Secondary Education impacts the choice of disciplinary area, which relates to students' CT performance. Overall, CT differences may be mostly due to pedagogical practices, so "educators will need to study the practices of exemplary instructors rather than exemplary disciplines, because no disciplines appear to stand out in this domain" (Brint et al, 2012, p. 22).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the literature no differences in CT development across higher education programmes are reported. Evens, Verburgh, and Elen (2013) found differences in CT development during the first year of higher education between Flemish professional and academic bachelor students. Professional bachelor programmes prepare students for the labour market.…”
mentioning
confidence: 80%
“…The design of the study is visualized in Figure 1. Separate analyses were done for professional and academic bachelor programmes because there are differences in growth between the first years of both programme types (Evens et al, 2013). In order to facilitate comparability between the academic and the professional programmes, only bachelor students were included in the sample.…”
Section: Overall Designmentioning
confidence: 99%
“…Additionally, individuals with critical thinking skill are deemed much easier and flexible to adapt and overcome any situations where information seems to develop very fast (Dwyer, Hogan, & Stewart, 2014). Critical thinking skill also helps students cope with numerous challenges that somehow occur in their personal and career life in the future (Evens, Verburgh, & Elen, 2013). For that reason, empowering critical thinking skill will get students prepared to deal with unpredictable development as it happens today (Scott, 2015).…”
Section: Introductionmentioning
confidence: 99%